2022
DOI: 10.3390/cancers14215468
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling as a Driver of Stemness and Metabolic Reprogramming in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a major cause of cancer death worldwide due to its high rates of tumor recurrence and metastasis. Aberrant Wnt/β-catenin signaling has been shown to play a significant role in HCC development, progression and clinical impact on tumor behavior. Accumulating evidence has revealed the critical involvement of Wnt/β-catenin signaling in driving cancer stemness and metabolic reprogramming, which are regarded as emerging cancer hallmarks. In this review, we summarize the regulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 225 publications
0
13
0
Order By: Relevance
“…It likely collaborates with mitochondria and possibly other organelles and signaling pathways, such as β-catenin/WNT pathway as our study has shown, to maintain energy production in tumor cells under stress. β-catenin/WNT pathway, indeed, is well known for its involvement in glycolysis and metabolic reprogramming (49, 50). This provides an interesting future direction for exploring the mechanistic link between HKDC1 and liver cancer progression from the perspective of tumor-TME interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It likely collaborates with mitochondria and possibly other organelles and signaling pathways, such as β-catenin/WNT pathway as our study has shown, to maintain energy production in tumor cells under stress. β-catenin/WNT pathway, indeed, is well known for its involvement in glycolysis and metabolic reprogramming (49, 50). This provides an interesting future direction for exploring the mechanistic link between HKDC1 and liver cancer progression from the perspective of tumor-TME interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites were eluted within a 50 min gradient (buffer A: 0.2% formic acid in H2O; buffer B: 0.2% formic acid in acetonitrile). MS settings for both types of samples included MS1 scans (120,000 resolution, 100-1000 m/z, 3 x 10 6 AGC and 50 ms maximal ion time) and 20 data-dependent MS2 scans (30,000 resolution, 2 x 10 5 AGC, ∼45 ms maximal ion time, HCD, Stepped NCE (50, 100, 150), and 20 s dynamic exclusion). A quality control sample was injected in the beginning, middle and the end of the samples to monitor the system stability of LC-MS.…”
Section: Methodsmentioning
confidence: 99%
“…WNT3A and WNT9A are members of the Wnt gene family, which is known to be pivotal in cellular proliferation, differentiation, maintenance of liver homeostasis, and facilitation of adult tissue repair. 82 , 83 Further investigation is needed to define the mechanism of the SNP in protecting from HCC in people who use alcohol.…”
Section: Genetic Associations For Hepatocellular Carcinomamentioning
confidence: 99%
“…In the presence of oxygen, tumor cells exhibit high levels of glycolysis that provide energy for the metabolic activity of the cell, known as aerobic glycolysis or the Warburg effect ( 8 ). High levels of aerobic glycolysis, accompanied by massive glucose consumption and massive lactate production, confer proliferation, invasion and drug resistance advantages in tumor cells ( 9 ). Targeting enzymes related to glycolysis in HCC may be a selective therapeutic strategy ( 10 ).…”
Section: Introductionmentioning
confidence: 99%